2021
DOI: 10.1016/j.omtm.2021.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of key genes as novel biomarkers specifically associated with HPV-negative cervical cancer

Abstract: Cervical cancer is a common female malignancy that is mainly caused by human papillomavirus (HPV) infection. However, the incidence of HPV-negative cervical cancer has shown an increasing trend in recent years. Because the mechanism of HPV-negative cervical cancer development is unclear, this study aims to find the pattern of differential gene expression in HPV-negative cervical cancer and verify the underlying potential mechanism. Differentially expressed genes were compared among HPV-positive cervical cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 47 publications
(45 reference statements)
0
19
0
Order By: Relevance
“…Interest in HPV independent cervical cancer has increased in recent years 5–10. Data published on head and neck cancer, as well as improvements in histological diagnosis using molecular characterization, have contributed to this interest 30–34. Controversy concerning HPV independent cervical cancer exists relating to the heterogeneity of stage and histotypes throughout these studies, as well as differences in therapeutic approaches, poor quality of tissue samples, and differences among HPV detection methods 35…”
Section: Discussionmentioning
confidence: 99%
“…Interest in HPV independent cervical cancer has increased in recent years 5–10. Data published on head and neck cancer, as well as improvements in histological diagnosis using molecular characterization, have contributed to this interest 30–34. Controversy concerning HPV independent cervical cancer exists relating to the heterogeneity of stage and histotypes throughout these studies, as well as differences in therapeutic approaches, poor quality of tissue samples, and differences among HPV detection methods 35…”
Section: Discussionmentioning
confidence: 99%
“…For example, in cholangiocarcinoma, high expression of TTYH3 accelerated ETM transformation and promoted malignant behavior of cholangiocarcinoma cells [37]. In ovarian cancer, cervical cancer, and colorectal cancer, elevated expression of TTYH3 also predicted poor prognosis [38][39][40]. Interestingly, we found that overexpression of TTYH3 also evidently facilitated the malignant phenotype of BC, manifested by enhanced proliferative and metastatic abilities.…”
Section: Discussionmentioning
confidence: 64%
“…Also, the cancer genome atlas (TCGA) includes several HPV-negative cervix carcinomas [ 15 ]. Studies have shown that gene expression profiles of these cancers are distinct from those of HPV-positive cervical cancers, providing evidence that HPV-negative cervical cancers comprise a separate entity [ 43 ]. These cancers will be missed in screening programs that use HPV screening as a primary test.…”
Section: Discussionmentioning
confidence: 99%